In pursuit of belonging : forging an ethical life in European-Turkish spaces - Rottmann, Susan Beth (Anthropology of Europe (Series), 2019)
Belonging is a not a state that we achieve, but a struggle that we wage. The struggle for belonging is more difficult if one is returning to a homeland after many years abroad. In Pursuit of Belonging is an ethnography of Turkish migrants' struggle for understanding, intimacy and appreciation when they return from Germany to their Turkish homeland. Drawing on an established tradition of life story writing in anthropology, Rottmann conveys the struggle to forge an ethical life by relating the experiences of a second-generation German-Turkish woman named Leyla.